Formulasi Dan Uji Stabilitas Sediaan Stick Moisturizer Dari Ekstrak Pagagan (Centella Asiatica) - Ardi Yurlanda; Fajrian Aulia Putra (Universitas Sumatera Barat, 2026)
Centella asiatica, also known as gotu kola, contains triterpenoids and flavonoids that function as natural antioxidants and moisturizers. This study formulated three stick moisturizer preparations F0 as a control without extract, F1 containing 3% extract, and F2 containing 5% extract to evaluate the effect of active ingredient concentration on product quality. The formulations were assessed over six storage cycles through organoleptic testing, homogenity, pH, irritation, skin hydration, and hedonic evaluation. The results showed that F0, F1, and F2 maintained a stable light-green color, soft texture, and consistent aroma without significant changes during storage. The pH values of all three formulas remained within the safe range for skin (5.6–6.9) and did not cause irritation. Hydration testing indicated that both F1 and F2 increased skin moisture levels, with F2 producing the highest improvement. Hedonic evaluation also revealed that panelists preferred F2 in terms of aroma and texture. Overall, the three formulas demonstrated good physical stability and were well accepted, with F2 showing the best performance.